2012
DOI: 10.1186/1743-422x-9-43
|View full text |Cite
|
Sign up to set email alerts
|

Biology and interactions of two distinct monopartite begomoviruses and betasatellites associated with radish leaf curl disease in India

Abstract: BackgroundEmerging whitefly transmitted begomoviruses are major pathogens of vegetable and fibre crops throughout the world, particularly in tropical and sub-tropical regions. Mutation, pseudorecombination and recombination are driving forces for the emergence and evolution of new crop-infecting begomoviruses. Leaf curl disease of field grown radish plants was noticed in Varanasi and Pataudi region of northern India. We have identified and characterized two distinct monopartite begomoviruses and associated bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 56 publications
0
34
0
Order By: Relevance
“…Recombination has been reported to be the major factor in the emergence of begomoviruses infecting crops and weeds in India Kumari et al, 2010;Singh et al, 2012). Begomoviruses associated with chilli and tomato contributed to 32 out of the 44 recombination events detected in ChiLCD-associated begomoviruses, and the remaining recombination events (12/44) were associated with yet undescribed or non-solanaceous-cropinfecting begomoviruses.…”
Section: Discussionmentioning
confidence: 99%
“…Recombination has been reported to be the major factor in the emergence of begomoviruses infecting crops and weeds in India Kumari et al, 2010;Singh et al, 2012). Begomoviruses associated with chilli and tomato contributed to 32 out of the 44 recombination events detected in ChiLCD-associated begomoviruses, and the remaining recombination events (12/44) were associated with yet undescribed or non-solanaceous-cropinfecting begomoviruses.…”
Section: Discussionmentioning
confidence: 99%
“…Based on genome organization, they are further classified as either monopartite (DNA A -like component) or bipartite (DNA A and DNA B components) encoding 5-7 proteins necessary for viral replication, movement and pathogenesis (Fauquet and Stanley, 2003;Fauquet et al, 2008). In addition, monopartite begomoviruses infecting both crops as well as weeds are often associated with satellite and satellite-like molecules named as betasatellites and alphasatellites, respectively (Briddon et al, 2003;Saunders et al, 2008;Chattopadhyay et al, 2008;Kumar et al, 2012;Singh et al, 2012). Recently, association of satellite molecules has also been reported with bipartite begomoviruses (Romay et al, 2010;Sivalingam and Varma, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Kumar et al (2012) observed the upward curling, crinkling, puckering, reduction of leaf area along with stunting of whole plant in the plants of chilli infected with leaf curl disease. Leaf curl type of symptoms in radish associated with radish leaf curl disease in Northern parts of India has been reported by Singh et al (2012).…”
Section: Resultsmentioning
confidence: 99%